The characteristics and role of informal leaders in work groups : a South African perspective - Wienekus, Barend Willem (Rhodes University, Faculty of Commerce, Investec Business School, 2010)
It has been twenty years since F W De Klerk unbanned the African National Congress. This momentous occasion changed overnight the business landscape in South Africa and the way business were done for many decades. Before and after this crucial moment in South African history, leaders played a significant role in bringing change about as well as managing it. Whether hierarchical or non-hierarchical, leadership manifests itself through all spheres of civilisation. Within any collective, formal as well as informal leadership are always at work and within the environment there always seems to be an individual that appears to hold equal or more influence and sway over the collective. This research investigates the characteristics and role of this individual, the informal leader. In addition, against the melting pot of the diversity of culture, social structures, economics, and demographics in South Africa, the influence of culture on how leadership is being perceived and experienced is also researched. The research is grounded in a post-positivists approach and conducted within a constructivist-interpretative paradigm. A qualitative approach is followed with personal interviews as the method to collect the data from respondents. The interview protocol consists of a combination of questions containing questions of both a quantitative and qualitative nature. Questions of a qualitative nature were open-ended and of an in-depth nature. The research is two pronged. The focus of the research is an Original Equipment Manufacturer (OEM) in the South African Motor Industry and for the primary goal of the research data was collected from employees within work groups of the OEM. The primary research goal investigates the role and characteristics of informal leaders in work groups as seen and experienced by their fellow employees and if there is any congruence with that of the role and characteristics of formal leaders. The study found no fundamental differences between the characteristics and role of formal and informal leaders. The characteristics and role of leaders between different cultures also appear to be the same. For the secondary research goal "“ determining whether the role and characteristics of informal leaders in work groups could be underpinned in the principles of Ubuntu and if consideration should be given to any cultural differences between leaders and followers by organisational hierarchies "“ the literature was reviewed in order to reach a conclusion with regards this goal. The literature indicates that culture does affect leadership, especially on how the leadership is executed and experienced in a multicultural society and if ignored, will have a detrimental effect on effective leadership. In order to strive towards achieving maximum productivity, it is imperative that management in South African organisations be aware of the changed dynamic within their organisations as well as on the global stage. The research therefore ends with the practical implications of informal leaders for organisations in South Africa. It is recommended that the importance and contribution of informal leaders within work groups in a multi-culture organisation needs not only to be considered as an element of group leadership, but should be accommodated by the organisation. It is also recommended that organisations recognise the cultural differences between leaders and followers in organisations and the possible consequences if ignored. If the competitive pressures and requirements of globalisation are ignored against the background of Afrocentric expectations and motivational imperatives of the South African workforce, it will result in an ineffective workforce, which will in due course render these organisations uncompetitive and non-sustainable locally and globally.
Keywords: Supervisors, industrial -- South Africa; Leadership -- South Africa